2008
DOI: 10.1021/ja711283c
|View full text |Cite
|
Sign up to set email alerts
|

Light-Controlled Supramolecular Helicity of a Liquid Crystalline Phase Using a Helical Polymer Functionalized with a Single Chiroptical Molecular Switch

Abstract: Control over the preferred helical sense of a poly(n-hexyl isocyanate) (PHIC) by using a single light-driven molecular motor, covalently attached at the polymer's terminus, has been accomplished in solution via a combination of photochemical and thermal isomerizations. Here, we report that after redesigning the photochromic unit to a chiroptical molecular switch, of which the two states are thermally stable but photochemically bistable, the chiral induction to the polymer's backbone is significantly improved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(154 citation statements)
references
References 60 publications
3
147
0
4
Order By: Relevance
“…In the cases of 1b and 1c, removal of the solvent by evaporation led to a viscous oil, and deracemization was not observed (entries 3 and 6). In previous experiments involving deracemization by salt formation in the solution phase, it was demonstrated that external chiral stimuli induced a helical sense in a dramatically optically active helical polymer or oligomer [49][50][51][52][53][54]. In our experiment, the axial chirality of 1a-c could not be controlled in the solution phase because the chiral acid in the salt was located far from the axial chiral auxiliary.…”
Section: Resultsmentioning
confidence: 59%
“…In the cases of 1b and 1c, removal of the solvent by evaporation led to a viscous oil, and deracemization was not observed (entries 3 and 6). In previous experiments involving deracemization by salt formation in the solution phase, it was demonstrated that external chiral stimuli induced a helical sense in a dramatically optically active helical polymer or oligomer [49][50][51][52][53][54]. In our experiment, the axial chirality of 1a-c could not be controlled in the solution phase because the chiral acid in the salt was located far from the axial chiral auxiliary.…”
Section: Resultsmentioning
confidence: 59%
“…such as small organic molecules [13][14][15][16][17][18][19], polymers [20][21][22][23], metamaterials [24], and assemblies [25][26][27][28], have been developed for chirality induction and switching in response to external stimuli, more sophisticated systems are required to mimic natural systems.…”
Section: Open Accessmentioning
confidence: 99%
“…In general, UV irradiation or circularly polarized light (CPL) is introduced as a light stimulus to mediate and enhance the chiral effects of materials. In the exquisite study presented by Pijper et al 37 in 2008, UV light was utilized as a stimulus to mediate the chirality of a helix. The authors attached a chiroptical switching molecule at the end of a poly(n-hexyl isocyanate) chain that worked as a light-driven motor.…”
Section: Photo-mediated Transformationmentioning
confidence: 99%